Age-specific relationship between HIV and TB treatment outcomes in the West Region of Cameroon: a cross-sectional study - Solange Mudih Ngala; Disline Manli Tantoh; Oswald Ndi Nfor; Gamo Djouomo Francis; Adeline Fitame; Yen-Wei Chu (BMC Infectious Diseases)
Abstract Background Co-infection with Mycobacterium tuberculosis (M. tuberculosis) and Human Immunodeficiency Virus (HIV) poses significant global public health challenges, with varying impacts across age cohorts. Evaluating tuberculosis (TB) treatment outcomes, especially among HIV patients across different age groups, is crucial for effective TB management. This study assessed the age-specific relationship between HIV status and TB treatment outcomes among TB patients in Cameroon. Methods This cross-sectional study included 2,455 TB patients receiving treatments in the West Region of Cameroon between January 2015 and December 2019. Data were extracted from National Tuberculosis Program Registers. The association of TB treatment outcomes with HIV and age was assessed using multivariate logistic regression. Results TB-HIV co-infection was significantly associated with lower TB treatment success. For HIV patients on antiretroviral therapy (ART), the odds ratio (OR) was 0.463 (95% confidence interval [CI]: 0.367–0.583, Bonferroni-adjusted P < 0.001). For HIV patients not on ART, the OR was 0.077 (95% CI: 0.030–0.200, Bonferroni-adjusted P < 0.001). A significant trend (P < 0.001) further indicated a consistent association between TB-HIV co-infection and treatment status. Older age was significantly associated with slightly lower treatment success (OR: 0.976; 95% CI: 0.969–0.983, Bonferroni-adjusted P < 0.001). TB-HIV co-infection remained significantly associated with lower TB treatment success after age categorization (OR; 95% CI, Bonferroni-adjusted P = 0.498; 0.394–0.631, < 0.001 for HIV patients on ART and 0.081; 0.032–0.210, < 0.001 for those without ART). The interaction between age and HIV was significant (P < 0.001). Age stratification revealed a significantly lower treatment success among HIV patients aged 25 and above, especially those not taking ART: OR (95% CI, Bonferroni-adjusted P) = 0.101 (0.032–0.312, < 0.001) and 0.038 (0.004–0.322, 0.025) for 25–44 and ≥ 45 years, respectively. Conclusion In this study, HIV status and older age were jointly associated with lower TB treatment success. Notably, treatment success was lower among HIV-positive patients aged 25 and above, especially those not on ART. Effective patient management, routine follow-up, and integration of TB and HIV services could improve TB treatment outcomes, particularly among adult HIV patients not taking ART. Trial registration Not applicable. This study is observational.